2011
DOI: 10.5005/jp-journals-10024-1043
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Change of Elastomeric Materials after Immersion in Disinfectant Solutions for Different Times

Abstract: Aim The aim of this study was to evaluate the influence of immersion period in two disinfectant solutions on dimensional change of four elastomeric impression materials. Materials and methods Four representative materials of each class of elastomers: Xantopren (polydimethylsiloxane—PDS), Express (polyvinyl siloxane—PVS); Permlastic (polysulfide— PS) and Soft Impregum (polyether—EP) were mixed according to manufacturers’ instructions and then inserted into a metal matrix prepared according to the specificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 23 publications
0
39
0
1
Order By: Relevance
“…Evaluating the influence of immersion period in disinfectant solutions on dimensional change of elastomers, Carvalhal et al 22 note that there are time limits within disinfection which must be performed, because of the reactivity of disinfecting agents. They also emphasize that in shorter immersion periods, sodium hypochlorite solution lead to greater dimensional change of condensation silicone (Xantopren) compared with glutaraldehyde, which is in accordance with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating the influence of immersion period in disinfectant solutions on dimensional change of elastomers, Carvalhal et al 22 note that there are time limits within disinfection which must be performed, because of the reactivity of disinfecting agents. They also emphasize that in shorter immersion periods, sodium hypochlorite solution lead to greater dimensional change of condensation silicone (Xantopren) compared with glutaraldehyde, which is in accordance with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A third limitation is that the prescribed measurements were recorded on a flat surface, disregarding the possibility of dimensional changes in three dimensions. Some studies have used this method 4,21,22 , while the other authors [23][24][25] have introduced different modifications.…”
Section: Discussionmentioning
confidence: 99%
“…[1719] A number of methods for disinfection have been investigated and recommended including antimicrobial immersion system and/or spraying and then sealing in a bag or spraying system. It has been suggested that immersion system is better than spraying as the latter leads to the pooling effect and its effect is localized.…”
Section: Discussionmentioning
confidence: 99%
“…[1314] Much work has been undertaken, and results have been reported regarding the surface changes and dimensional stability of the impression material that is subjected to different immersion disinfectants. [111516171819]…”
Section: Introductionmentioning
confidence: 99%
“…As well as, it is commonly used for preliminary impressions to obtain a study cast used for treatment planning, diagnostic purposes, construction of custom trays or provisional prostheses (2) . Dental impression is considered as a remarkable way for transmission of microorganisms like hepatitis B,tuberculosis or AIDS from the office to other environments because of its contact with saliva and blood during the impression procedure (3,4) .…”
Section: Introductionmentioning
confidence: 99%